Merging the Self-Determination Theory and the Broaden and Build Theory through the nexus of positive affect: A macro theory of positive functioning. (January 2023) - Stanley, Peter J.; Schutte, Nicola S.
Abstract: The Macro Theory of Positive Functioning integrates key aspects of the Self-Determination Theory and the Broaden and Build Theory. The theory posits a model that provides new perspectives on the development of positive characteristics. The Macro Theory proposes that higher levels of intrinsic motivation and basic needs satisfaction as described by the Self-Determination Theory result in high levels of positive affect (consisting of emotions such as joy). The Broaden and Build Theory proposes that high levels of positive affect result in a broadening of perspective resulting in more engagement with opportunities and relationships, which builds beneficial cognitive and behavioural resources and skills. Such resources and skills may manifest as positive characteristics described and studied in the positive psychology approach. These characteristics include self-compassion, self-efficacy, empathy, emotional intelligence, and character strengths. High levels of these characteristics may result in optimal functioning. Results from model testing with concurrent data designs as well as experimental designs provide initial support for the Macro Theory. Highlights: A macro theory of positive affect and associated research is presented. The theory draws on self-determination and broaden and build concepts. The theory emphasises the sequential origins and consequences of positive affect. Intrinsic motivation and basic needs satisfaction result in positive affect. Positive affect facilitates building positive characteristics.